A Study on Challenges Faced by Commerce Students in Higher Secondary Level - R., Indumathi; Selvakumar, Y. Stanly (Journal of Advanced Research in English & Education, 2023)
To learn about business, trade, industry, and commerce, one should pursue a degree in commerce. It gives the knowledge necessary for a variety of professional and specialised business studies. Due to the fact that commerce education is offered outside of the school day in India, pupils were not taught these subjects in school and lack a working grasp of business and finance. Students studying commerce have access to a variety of courses that help them develop the skills and information needed for employment in many industries. However, because schools, universities, and other institutions did not have enough teachers or practical training to prepare students for the workforce, they did not have the necessary knowledge and skills. Everything in the world now is digital, and this includes education. In order to accomplish the goals of commerce education, modern education also adopted the online learning environment and MOOCs platform. For those who work in good managerial positions, there are many professional prospects available for students of commerce, including CA, CMA, CS, and others. There are also several difficulties, which are described in depth throughout the study. The problems require appropriate solutions, which are typically provided by schools, universities, and other institutions with the aid of talented faculty. Because of the root tree stands, the faculties resemble roots. “Trees are capable of growing deep roots but root is strongly influenced by soil and climate condition.” Similar to this, professors are the foundation who have great topic knowledge and enable students to expand their knowledge and comprehension about subjects to grow in their lives.